Noise temperature of the electromagnetic waves in the mid-latitude ionosphere - Guzel, Esat; Canyilmaz, Murat (Elsevier, 2021)
In this theoretical study, the noise temperature of the different modes (ordinary, extraordinary, right and left polarized) of the electromagnetic wave travelling vertically in the ionosphere has been investigated for the solstice and the equinox days, 2015. The noise temperature values vary between 10(-6) and 10(-2) K for all results. There is a slight decrease in the noise temperature values near the 105 km and then a rise again for 4, 5, 6 MHz waves at all modes. As the frequency of the wave increases, the noise temperature values change periodically depending on the electron density. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Noise temperature; Mid-latitude ionosphere; Electromagnetic wave propagation